2011
DOI: 10.1021/jz200057g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrophilic Surfaces on Interfacial Water Dynamics Probed with NMR Spectroscopy

Abstract: In suspensions of Nafion beads and of cationic gel beads, NMR spectroscopy showed two water–proton resonances, one representing intimate water layers next to the polymer surface, the other corresponding to water lying beyond. Both resonances show notably shorter spin–lattice relaxation times (T1) and smaller self-diffusion coefficients (D) indicating slower dynamics than bulk water. These findings confirm the existence of highly restricted water layers adsorbed onto hydrophilic surfaces and dynamically stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…They found two water proton resonances indicating two distinct and magnetically unique water species. According to the authors [66], although the chemical shift is similar to that of the bulk (0.2 ppm), T1 and the self-diffusion coefficient values could be identifiers of the restricted long-range nature of EZ water.…”
Section: Large-scale Inhomogeneities In Aqueous Systems And/or Exclusmentioning
confidence: 98%
See 1 more Smart Citation
“…They found two water proton resonances indicating two distinct and magnetically unique water species. According to the authors [66], although the chemical shift is similar to that of the bulk (0.2 ppm), T1 and the self-diffusion coefficient values could be identifiers of the restricted long-range nature of EZ water.…”
Section: Large-scale Inhomogeneities In Aqueous Systems And/or Exclusmentioning
confidence: 98%
“…They bear a negative charge of as much as 150-200 mV near the nucleating surface, exhibit increased dynamic viscosity and show diminished IR emissivity and smaller T2 relaxation times [62] and seem to be expanded by light [65]. Yoo et al [66] studied EZ water by NMR spectroscopy to measure chemical shifts, spin-lattice (T1) relaxation and the self-diffusion coefficient of interfacial water. They found two water proton resonances indicating two distinct and magnetically unique water species.…”
Section: Large-scale Inhomogeneities In Aqueous Systems And/or Exclusmentioning
confidence: 99%
“…This theory has been debated [5] and needs experimental testing. Although the EZ has been characterized by numerous experimental approaches [1,[6][7][8][9][10][11][12][13][14][15][16][17][18], key features related to its thermodynamics and kinetics still need to be investigated. In the present work we measured the short-and long-time-scale kinetics of EZ formation in specially designed microfluidic devices that reduce unwanted local perturbation effects, estimated the magnitude of the exclusion force, and tested key predictions of the most plausible microscopic mechanisms of EZ formation.…”
Section: Introductionmentioning
confidence: 99%
“…Pollack group at the University of Washington (Seattle, WA, USA), the spatial scale of the water layer adjacent to the Nafion interface, where the water is believed to be structured, can amount to hundreds of microns [5][6][7][8][9][10][11][12][13]. Particularly, it was shown that near to the "Nafion-polar liquid" a so-termed "exclusion zone (EZ)" interface is formed from the liquid side; the macroscopic characteristics of this area essentially differ from those in the bulk liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion zones have also been seen close to collagen gels and vascular endothelium, which was found by using both colloid microspheres and erythrocytes. This fact has allowed the authors of [5][6][7][8][9][10][11][12][13] to assume that the EZ effect should be observed for a wide class of hydrophilic substrates.…”
Section: Introductionmentioning
confidence: 99%